The use of interactive data visualisation technology in cultural digital heritage display using edge computing. (14th July 2022) - Zhao, Xinjie
The purpose is to solve the survival dilemma of intangible cultural heritage caused by economic growth and social ecological environment changes in recent years, so as to protect and inherit the intangible cultural heritage scientifically. With Chinese folk dance as an example, the display and inheritance of cultural heritage are studied. Virtual reality, interactive data visualisation and the computer technology of edge computing are used to analyse the characteristics of digital folk dance activities. Then, the design of the real touching face generation and body interaction structure of folk dance inheritors is completed. In the visual analysis and inheritance of folk dance, considering that face matching is an important step, a new face matching algorithm is proposed based on edge computing. The simulation results show that the accuracy of the new face matching algorithm is as high as 98%, and the average matching time is reduced to 1.79 s. The optimisation of face matching algorithm is of great value to realise the visualisation and inheritance of traditional folk dance cultural heritage. This exploration promotes the development and application of digital technology of intangible cultural heritage in China, and is of great significance to the innovation and comprehensive protection of intangible cultural heritage.